(untitled) (Global Journal of Medical Research, 2021)
The rehabilitation of patients with dental implants can be a challenging and meticulous procedure. Due to the anatomic variations in different patients a standardized treatment approach cannot be followed. From the initial diagnosis itself the practioner must plan the case bearing the eventual end in mind in order to provide the patient with a prosthesis that serves both purposes of functionality as well as esthetics. This article aims to highlight certain parameters such as available bone, bone densities, remaining ridge heights, tooth proportions, number of implants and the positions that the teeth would assume that would dictate the type of prosthetic options available to the patient. It would further aid the clinician to decide a stepwise treatment approach and in turn help in communication with the dental laboratory as well as the patient.